ANALISIS KUALITAS PELAYANAN PERUSAHAAN DAERAH AIR MINUM (PDAM) TIRTA ALAMI KABUPATEN KEPAHIANG - -, Arminsyah; Anitasari, Merri (Ekombis Review, 2014)
Arminsyah, Merri Anitasari;An Analysis Of Services Quality at Drinking Water Company (PDAM) Tirta Alami Kepahiang. This research aims to investigate the quality of Services at drinking water Company (PDAM) Natural Tirta Kepahiang. This research then used questionnaire as the data collecting method. Quantitative analysis then also be used as a techniques for data analysis by using weighted average value formula formed by Men Pan decree Number KEP/25/m. PAN/2/2004 on the 14 items that are observed. From thequestionnaire it was obtained that the highest average of services is on the ease of servicing requirementswith a value of 3.03. While the lowest average value of service is on the services equity which gain a score 2.95. For IKM value,it get 63 which places between 62.51-81.25. This score means that the performance of PDAM Tirta Alami Kepahiang is good.Kata kunci:Kualitas Pelayanan